Source of Inflation in Saudi Arabia: An Empirical Study between 1989 and 2019 - Alabdulwahab, Sami Zaki (The Arab Journal of Administration, 2025)
Inflation is one of the economic indicators that helps decision makers to draw their economical strategies to control the economical activities. Also, inflation can be controlled by using the appropriate economical tools to direct the economy in the short-run and long-run. Saudi Arabia is not any different from other countries in term of economical challenges, especially with a degree of economical openings to the rest of the world. However, the economical opening brings challenges and one of those challenges is the local prices fluctuations could be observed via exports and imports. Furthermore, local factors could affect the prices in the economy in general. The ARDL cointegration method will be used to test the long-run relationship among the variables in the focused study. The result indicates that there is a long-run relationship among the inflation and the independent variables. The long-run relationship is significant between inflation and imports prices, exports prices, money supply, government expenditure, nominal effective exchange rate as well the non-oil GDP. On the other hand, there is a dynamic relationship in the short-run between inflation and exports prices, non-oil GDP, oil rent as well as world price level. However, inflation is affected by the world factors in the short-run and the long-run yet the local factors more dominate in affecting the inflation in Saudi Arabia. Also, the non-oil GDP has a greater positive impact on inflation relatively to the rest of the variables in the model.